Acellular Dermal Matrix as a Core Strut for Projection in Nipple Reconstruction: Approaches for Three Different Methods of Breast Reconstruction - Park, Gui-Yong; Yoon, Eul-Sik; Cho, Hee-Eun; Lee, Byung-Il; Park, Seung-Ha (Archives of Plastic Surgery, 2016)
Background The objective of this paper was to describe a novel technique for improving the maintenance of nipple projection in primary nipple reconstruction by using acellular dermal matrix as a strut in one of three different configurations, according to the method of prior breast reconstruction. The struts were designed to best fill the different types of dead spaces in nipple reconstruction depending on the breast reconstruction method.Methods A total of 50 primary nipple reconstructions were performed between May 2012 and May 2015. The prior breast reconstruction methods were latissimus dorsi (LD) flap (28 cases), transverse rectus abdominis myocutaneous (TRAM) flap (10 cases), or tissue expander/implant (12 cases). The nipple reconstruction technique involved the use of local flaps, including the C-V flap or star flap. A 1×2-cm acellular dermal matrix was placed into the core with O-, I-, and L-shaped struts for prior LD, TRAM, and expander/implant methods, respectively. The projection of the reconstructed nipple was measured at the time of surgery and at 3, 6, and 9 months postoperatively.Results The nine-month average maintenance of nipple projection was 73.0%±9.67% for the LD flap group using an O-strut, 72.0%±11.53% for the TRAM flap group using an I-strut, and 69.0%±10.82% for the tissue expander/implant group using an L-strut. There were no cases of infection, wound dehiscence, or flap necrosis.Conclusions The application of an acellular dermal matrix with a different kind of strut for each of 3 breast reconstruction methods is an effective addition to current techniques for improving the maintenance of long-term projection in primary nipple reconstruction.
Keywords: Acellular dermis; Nipples; Mammaplasty